Efficacy of Fecal Microbiota Transplantation in Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis. (July 2019) - Xu, Dabo; Chen, Vincent L.; Steiner, Calen A.; Berinstein, Jeffrey A.; Eswaran, Shanti; Waljee, Akbar K.; Higgins, Peter D.R.; Owyang, Chung
Abstract : OBJECTIVES: Irritable bowel syndrome (IBS) is a common gastrointestinal condition with a heterogeneous pathophysiology. An altered gut microbiome has been identified in some IBS patients, and fecal microbiota transplantation (FMT) has been suggested to treat IBS. We performed meta-analyses and systematic review of available randomized controlled trials (RCTs) to evaluate the efficacy of FMT in IBS. METHODS: We performed a systematic literature search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science. Selection criteria included RCTs of FMT vs placebo using FMT excipients or autologous FMT in IBS. Meta-analyses were conducted to evaluate the summary relative risk (RR) and 95% confidence intervals (CIs) of combined studies for primary outcome of improvement in global IBS symptoms as measured by accepted integrative symptom questionnaires or dichotomous responses to questions of overall symptom improvement. RESULTS: Among 742 citations identified, 7 were deemed to be potentially relevant, of which 4 studies involving 254 participants met eligibility. No significant difference in global improvement of IBS symptoms was observed at 12 weeks in FMT vs placebo (RR = 0.93; 95% CI 0.48–1.79). Heterogeneity among studies was significant ( I 2 = 79%). Subgroup analyses revealed benefits of single-dose FMT using colonoscopy and nasojejunal tubes in comparison with autologous FMT for placebo treatment (number needed to treat = 5, RR = 1.59; 95% CI 1.06–2.39; I 2 = 0%) and a reduction in likelihood of improvement of multiple-dose capsule FMT RCTs (number needed to harm = 3, RR = 0.54; 95% CI 0.34–0.85; I 2 = 13%). Placebo response was 33.7% in nonoral FMT RCTs and 67.8% in capsule FMT RCTs. The Grading of Recommendations Assessment, Development and Evaluation quality of the body of evidence was very low. DISCUSSION: Current evidence from RCTs does not suggest a benefit of FMT for global IBS symptoms. There remain questions regarding the efficacy of FMT in IBS as well as the lack of a clean explanation on the discrepant results among RCTs in subgroup analyses.